Analisis Determinan yang Berhubungan dengan Partisipasi Pria Menjadi Akseptor Program Keluarga Berencana di Indonesia (Analisis Data SDKI Tahun 2017) - Puspa Sari; Christin Angelina Febriani; Achmad Farich (LPPM Hang Tuah Pekanbaru, 2023)
Family planning programs have a role in reducing the risk of maternal death through the prevention of pregnancy, delaying gestational age, and determining the spacing of their pregnancies. Men can share roles by participating in family planning and reproductive health issues. The coverage of the use of family planning methods/methods among married men includes MOM (0.2%), condoms (3.1%), and traditional methods such as interrupted intercourse (2.9%) and periodic abstinence (1.1%). This study aims to determine the determinant factors of male participation as family planning acceptors in Indonesia (2017 IDHS Data Analysis). This research was quantitative with an analytic design and cross-sectional approach. The population of this study was all married men aged 15-54 years old in Indonesia in 2017. The sampling technique used was purposive sampling. Data analysis in this study used univariate, bivariate (chi-square), and multivariate (multiple logistic regression). The results of this study showed that there was no relationship between employment status (p = 0.197), there was no relationship between age (p = 0.0167), and there was a relationship between education (p = 0.001), economic status (p = 0.001), and area of ​​residence (p=0.001; OR=3,7) with men's participation as family planning acceptors. The factor that is most related to the men's participation as family planning acceptors was the economic variable. Suggestions for the government to make regulations and socialization, in order that community no longer considered that being a family planning acceptor was the women's duty.